2013
DOI: 10.21608/ejar.2013.165104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effects of Silver Nanoparticles Against Rice Blast Disease Caused by Magnaporthe Grisea

Abstract: Rice blast disease, caused by Magnaporthe grisea, is the most serious biotic threat to rice (Oryza sativa L.) production worldwide.It causes severe yield losses in Egypt especially in epidemic years. The fungus is highly variable so disease control is a challenge. In this study, the effect of silver nanoparticles (20-30 nm) against rice leaf blast fungus was evaluated under different cultivation conditions both in vitro and in vivo. Under lab conditions, the application of four concentrations of silver nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Because this fungus has a variety of qualities that aid with agricultural commodities, Trichodermabased products contribute to more than half of the overall worldwide biopesticide industry employed for improving plant growth, nutrient use efficiency, and physiological response to both biotic and abiotic stresses [23]. The use of green AgNPs as an antifungal agent is seen as an environmentally benign resource, an alternative to fungicides, and a cost-effective method [24,25]. Based on updated literature, the primary goals of this investigation were to: (1) determine the ability of a cell-free extract from a T. harzianum natural biocontrol strain to act as a reducing agent and stabilizer in the production of AgNPs; (2) undertake physicochemical characterization to determine the structure, size, and morphology of the generated AgNPs; and (3) test the antifungal activity of AgNPs in vitro and in vivo against three fungal pathogens, namely, R. solani, F. fujikuroi, and M. phaseolina.…”
Section: Introductionmentioning
confidence: 99%
“…Because this fungus has a variety of qualities that aid with agricultural commodities, Trichodermabased products contribute to more than half of the overall worldwide biopesticide industry employed for improving plant growth, nutrient use efficiency, and physiological response to both biotic and abiotic stresses [23]. The use of green AgNPs as an antifungal agent is seen as an environmentally benign resource, an alternative to fungicides, and a cost-effective method [24,25]. Based on updated literature, the primary goals of this investigation were to: (1) determine the ability of a cell-free extract from a T. harzianum natural biocontrol strain to act as a reducing agent and stabilizer in the production of AgNPs; (2) undertake physicochemical characterization to determine the structure, size, and morphology of the generated AgNPs; and (3) test the antifungal activity of AgNPs in vitro and in vivo against three fungal pathogens, namely, R. solani, F. fujikuroi, and M. phaseolina.…”
Section: Introductionmentioning
confidence: 99%
“…The silver nanoparticles delayed and greatly inhibited fungal growth at low concentrations, according to radial growth measurements. 61 found that secondary metabolites extracted from C. elatum showed antifungal activity against P. oryzae with an ED 50 of 231ppm. 62 Conidia Germination Inhibition: Because fungi need a large number of germinated conidia to successfully infect plant tissue, inhibiting conidia germination is critical in reducing or preventing the formation of plant diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Rice blast is the most serious fungal diseases in Egypt. It is caused by Magnaporthe oryzae (Elamawi and El-shafey, 2013;Hassan et al, 2017). The asexual stage of this fungus is named Pyricularia oryzae (TeBeest et al, 2012) which is the only form that is mostly present in the field (Picco et al, 2001;Elamawi and El-shafey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by Magnaporthe oryzae (Elamawi and El-shafey, 2013;Hassan et al, 2017). The asexual stage of this fungus is named Pyricularia oryzae (TeBeest et al, 2012) which is the only form that is mostly present in the field (Picco et al, 2001;Elamawi and El-shafey, 2013). This form can infect all aerial parts of rice plant resulting in yield losses of over 50% in susceptible cultivars under favorable conditions (Dean et al, 2005;Wilson et al, 2009;Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%